Konsep Alam Semesta Dalam Perspektif Al-Quran dan Sains - Afifah, Gusti; Ayub, Syahrial; Sahidu, Hairunnisa (Mataram University, 2020)
This article was made to find out the relationship between Al-Quran and science, especially the concept of the universe. This research was conducted to determine the concept of the universe in view of the Al-Qur'an and science. This research is a library research using the thematic interpretation method, which collects readings that talk about the five human senses, determine the topic and conduct analysis with tahlili interpretation, and draw conclusions. The result is that all the concepts of the universe discovered by scientists were written and delivered by the Prophet Muhammad 1400 years ago in the holy book of Al-Quran. Al-Quran is always more advanced than science, but Al-Quran is not a science textbook, but Al-Quran is a guide for humanity in navigating the three dimensions of life, namely the dimensions of mortal, barzakh and the hereafter.Â Keywords: Al-Quran; Science; Universe